Propriedades nutricionais, reológicas e sensoriais de bebidas lácteas elaboradas a partir de leite de cabra, vaca e a sua mistura. - Gomes, Jacieny Janne Leite (2012)
Dairy beverage milks and whey from cow and goat milk, using fruit jelly, can be a viable alternative to adding value to this derivative to obtain a product with nutritional quality and palatability. With this study we sought to develop and evaluate the physico-chemical, rheological profile and the sensory attributes of dairy beverages obtained from the mixture of whey and goat milk and cow. In the experimental design were prepared three milk drinks called BLV (made with dairy beverage 70% milk and 30% cow's milk whey), BLM (made with dairy beverage 35% milk and 15% goat whey and 35% milk and 15% cow's milk whey) and BLC (dairy beverage made with 70% milk and 30% goat whey), guava jelly added. Were analyzed for microbiological and physico-chemical properties of raw materials (whey and milk). The dairy beverages were evaluated immediately after manufacturing on the total solids, protein, fat and lactose, and subjected to physico-chemical properties (acidity, pH, and lactose), syneresis and viscosity during storage under refrigeration (4 ° C) at 1, 7, 14, 21 and 28 days, but also sensory and microbiological tests at 1, 14 and 28 days of storage. The type of milk and time of storage affected the physicochemical properties of milk drinks. The BLM showed pH values, lactose and water holding capacity less than the BLC, the upper and BLV. The findings indicated no significant changes in most sensory attributes except for uniform appearance, consistency and viscosity and furthermore, showed an increase in acidity and a reduction in viscosity of the milk beverages during storage, confirming the results of the rheological analysis (apparent viscosity) of these beverages. The addition of guava jelly gave positive changes in rheological and sensorial, suggesting replacement of addition of solids and / or stabilizers in the production of dairy drinks. For practical applications, the development of dairy beverage prepared with the mixture of milk and serum from goat's milk and cow, and adding guava jam can be an attractive initiative to obtain a product with satisfactory nutritional quality and consumer acceptability.